2010
DOI: 10.1021/ja107622m
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Near-Resonant Charge Transfer Mechanism for Double-Stranded Peptide Nucleic Acid

Abstract: We present evidence for a near-resonant mechanism of charge transfer in short peptide nucleic acid (PNA) duplexes obtained through electrochemical, STM break junction (STM-BJ), and computational studies. A seven base pair (7-bp) PNA duplex with the sequence (TA)(3)-(XY)-(TA)(3) was studied, in which XY is a complementary nucleobase pair. The experiments showed that the heterogeneous charge transfer rate constant (k(0)) and the single-molecule conductance (σ) correlate with the oxidation potential of the purine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(84 citation statements)
references
References 49 publications
7
77
0
Order By: Relevance
“…The delocalization of holes over multiple bases suggests that the coherency of holes does not become fully washed out over a short distance, and the sequential hopping model must be modified to include this feature. This conclusion is consistent with the theory of Renaud and colleagues 18 for poly(A)-poly(T) DNA hairpins, and the theoretical analysis by Venkatramani and co-workers 40 for peptide nucleic acids and de Pablo et al 14 for λ-DNA. We also note that coherent superexchange is considered in the variable range hopping model of charge transfer in DNA developed by Yu and colleagues 41 and Renger and colleagues 42 (see Supplementary Fig.…”
Section: Resultssupporting
confidence: 88%
“…The delocalization of holes over multiple bases suggests that the coherency of holes does not become fully washed out over a short distance, and the sequential hopping model must be modified to include this feature. This conclusion is consistent with the theory of Renaud and colleagues 18 for poly(A)-poly(T) DNA hairpins, and the theoretical analysis by Venkatramani and co-workers 40 for peptide nucleic acids and de Pablo et al 14 for λ-DNA. We also note that coherent superexchange is considered in the variable range hopping model of charge transfer in DNA developed by Yu and colleagues 41 and Renger and colleagues 42 (see Supplementary Fig.…”
Section: Resultssupporting
confidence: 88%
“…In a similar fashion, in our case, the presence of Cu(II) may support an electronic state which is energetically close to the Fermi level of the electrodes (for a schematic 1D energy diagram see Figure S3, Supporting Information). The temperature independence of this process is further supported by results from a theoretical investigation by Segal et al,21 who showed that in the case of small barrier between the electrode and the bridge (in this case due to the presence of Cu(II) ion), an activationless process should be seen.…”
Section: Resultssupporting
confidence: 57%
“…This computational framework has been described in detail previously and shown to be effective in several previous studies of charge transport properties of small organic molecules. 4042 We outline the procedure for studying TP1 below. A more detailed description is provided in Sections S.3–S.5 of ESI †…”
Section: Methodsmentioning
confidence: 99%